Encyclopedia of applied electrochemistry - Ota, Ken-ichiro; Savinell, Robert F.; Kreysa, Gerhard (Springer New York, 2014)
While electrochemistry deals with the interrelation of electrical and chemical phenomena, applied electrochemistry is the interface between fundamental science and practical applications. It is vitally important for our industrial society of today and even more so for its future. A successful response to global challenges such as securing energy supply, developing energy-efficient and sustainable processes and materials, environmentally friendly technologies, or monitoring physiological processes for health care requires electrochemical research and engineering. The Encyclopedia of Applied Electrochemistry provides an authoritative compilation of entries dealing with all applied aspects of electrochemistry, including basic theoretical concepts, and instrumentation. As a unique, one-stop resource for sound and digested knowledge in this field, the Encyclopedia of Applied Electrochemistry comprises the first applications-oriented interdisciplinary work on the critical technologies underlying key advances such as energy efficiency (e.g. batteries for electric cars, etc.), green and sustainable chemical industries, new materials (corrosion resistant and low-friction), and biomedical sensors.